Ambulatory electrocardiogram monitoring for syncope and collapse: a comparative assessment of clinical practice in UK and Germany. Issue 12 (7th August 2018) - Sutton, Richard; Mears, Robin; Kohno, Ritsuko; Benditt, David
Abstract: Aims: Diagnostic ambulatory electrocardiogram (AECG) monitoring is widely used for evaluating syncope/collapse. In Europe, two sets of practice guidelines [National Institute for Health and Clinical Excellence (NICE) and European Society of Cardiology (ESC)] provide recommendations concerning optimal selection of AECG devices. However, whether practising physicians' select AECGs based on published guidelines is unclear. This study examined AECG use by Emergency Department (EDs) physicians and cardiologists in two European countries: Germany (D) and United Kingdom (UK). Methods and Results: A quantitative survey was undertaken in which 177 respondents participated (ED: UK 33, Germany 40; Cardiology: UK 54, Germany 50). The choice of AECG technology varied by specialty. Thus, among EDs, despite patients having daily symptoms, 20% (UK), 31% (D) of respondents chose an AECG other than Holter monitor. Conversely, when monitoring for infrequent events (<monthly), 15–30% (UK and D) indicated choice of 24–48 h Holter, 15–30% (UK and D) a conventional event recorder, and only ∼50% select an insertable cardiac monitor (ICM). Among cardiologists, 6% (UK), 10% (D) would not choose a Holter for daily symptoms but, for infrequent symptoms, ∼80% would select an ICM (UK and D). However, many cardiologists (UK and D) persist with Holters for infrequent events despite repeated failure of that technology to provide a diagnosis. Conclusions: In evaluation of syncope/collapse, most UK and German ED physicians and cardiologists use AECG's according to guidelines, but a substantial minority diverge from AECG guideline recommendations.